Helicobacter pylori Increasing Spread of An Inflammation Cells and Gastric Mucosal Atrophy in Gastritis Patients - Oktaviyanti, Ika Kustiyah; Widodo, Firman Aprilianto; Hafidza, Fadhil; Rosida, Lena; Wibowo, Agung Ary; Yuliana, Ida (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Helicobacter pylori (H. pylori) is a bacterium which could reason chronic gastritis and then has the capability to purpose gastric mucosal atrophy. The modifications within the degree of gastric mucosal atrophy have been appreciably correlated with the degree of risk of gastric cancer. The purpose of the observe turned into to research the relationship among H. pylori and the spread of inflammatory cellular infiltration and gastric mucosal atrophy in gastritis patients in Banjarmasin. Method The study was carried out in September-November 2021 using a cross-sectional method with purposive sampling, that is as many as 87 samples of histopathological slides of gastritis patients in the anatomical pathology laboratory of Sari Mulia Hospital, Banjarmasin for the period 2019. Research analysis used Kolmogorov-Smirnov. Slide preparations were stained with immunohistochemistry (IHC) and hematoxylin-eosin (HE). Inflammatory cellular clearance was measured the use of a scale from revised Sydney system and gastric mucosal atrophy become measured the use of the OLGA staging system. Results The results showed as many as 40 (45.98%) H.pylori-positive patients with the most chronic inflammatory cell infiltration in 24 (60%) patients at grade 3 (p<0.001) and for gastric mucosal atrophy as many as 29 (72, 50%) of patients at various stages (p<0.001). Conclusion H. pylori has a significant relationship with inflammatory cell infiltration and gastric mucosal atrophy. H. pylori-positive causes a growth within the severity of inflammatory cellular irritation and mucosal atrophy in gastritis patients.